Penerapan Metode Diskusi Siswa Kelas IV pada Mata Pelajaran IPA SD Negeri Sewon Bantul Yogyakarta - Fifi Kharismah; Henry Aditya Rigianti (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research is motivated by the low understanding of learning methods that are not in accordance with the learning material. As a teacher, you should be good at choosing methods, techniques, and learning models so that the teaching and learning process can take place actively, creatively, effectively, and fun. While the obstacles from students include: low student motivation; student creativity in learning is still lacking. To improve students' competence in understanding the concept of root parts and their functions, it is necessary to use the "Discussion Method". By using the "Discussion Method" students' ability to understand the concept of root parts and their functions is expected to increase. Therefore, this study aims to contribute information and thoughts on how the "Discussion Method" is used in learning the root parts and their functions. In addition, to determine the increase in student achievement in science subjects. Thus, to obtain higher quality learning outcomes, it is necessary to use the "Discussion Method" in learning the root parts and their functions.